2010
DOI: 10.1097/mph.0b013e3181e90017
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pediatric Burkitt Lymphoma in Turkey

Abstract: This study aimed to assess the demographic data and treatment results of children who were diagnosed with Burkitt lymphoma and treated according to the Berlin-Frankfurt-Münster-95 (BFM) protocol in a single institution. A total of 48 patients (37 boys, 77%) with a median age of 8 years (range 2 to 16 years) at diagnosis, were evaluated. Primary tumor sites were abdomen (70.8%), head and neck (22.9%), peripheral lymph node (2%), bone (2%), and testis (2%). The 5-year overall survival (OS) and event-free surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 27 publications
3
11
1
Order By: Relevance
“…However, in one case interpreted provisionally as a secondary lymphoma, a late relapse could not be ruled out molecularly. Finally, patients with limited‐stage disease had very good outcomes, as reported with most series …”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…However, in one case interpreted provisionally as a secondary lymphoma, a late relapse could not be ruled out molecularly. Finally, patients with limited‐stage disease had very good outcomes, as reported with most series …”
Section: Discussionsupporting
confidence: 68%
“…Most of the drugs used to treat non‐Hodgkin lymphoma (NHL) are available in low‐ to middle‐income countries (LMICs). However, because of deficient supportive care in these countries, it is a common practice to reduce the dose intensity of protocols used by cooperative groups in high‐income countries . Even with such dose reductions, there are still many treatment‐related deaths in LMICs .…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, the sporadic form is more prevalent in male and older age than the endemic form. We observed that, nowadays, there was a decrease about age and male sex while comparing with the previous studies from our country [13][14][15][16][17][18][19][20] and GRAB group. We thought that there is a reverse alteration about sex and age by the course of time in Turkey, according to Ogwang et al [9] The primary intra-abdominal presentation is approximately 80% in the sporadic form [8,21,22], while primary jaw presentation is approximately 50% in the endemic form.…”
Section: Methodssupporting
confidence: 74%
“…BL constitutes approximately 40% of all childhood non-Hodgkin lymphomas in the United States (US) [8] and our finding (38.6%) is compatible with this. Examining previous studies from the same center and our country [13][14][15][16][17][18][19][20], the findings showed that the frequency of BL has decreased over time in Turkey.…”
Section: Discussionmentioning
confidence: 57%
“…Most reports from upper middle‐income countries (UMIC), usually regarding patients treated in referral institutions, showed that toxic mortality, especially during remission induction, is higher than in the protocols from major cooperative groups in HIC (Acquatella et al , ; Klumb et al , ; Celkan et al , ). In order to design an effective therapy for Burkitt lymphoma in LMIC, one must weigh the risk of toxic death against that of excess relapse when considering chemotherapy intensification.…”
Section: Management Of Burkitt Lymphoma In Low‐ and Middle‐income Coumentioning
confidence: 99%